Theoretical and Experimental Study of the Vibration of a Drum Type Washing Machine at Different Speeds - Shihab, Ibtisam Mahdi; Soud, Wafa Abd; Jebur, Nazik Abdulwahid (Al-Nahrain Journal for Engineering Sciences, 2017)
In the present work, theoretical and experimental Study of vibration of a drum type of Horizontal Washing Machine. The effect of the Isolators stiffness, damping coefficient and the drum mass for specific laundry capacity also has been studied. The work in this research has been carried out analytically by using MATLAB, and Study experimentally the effect of different speed and unbalance force during the spinning cycle of the washing machine at four sides of it. This analysis aims to reducing the excited vibration. This was achieved theoretically by investigate the effect of various parameters in order to assign property values to increase the isolation efficiency to reach optimum design. The results is show that drum vibration amplitude reduced to 42 % at spinning speed 1000 rpm and 41% at 1200, 1400 rpm when the applied selected parameters.